Adoption of agroforestry land use in semi arid Bundelkhand region â€“ A case study from Garhkundar-Dabarwatershed - Dhyani, S.K.; Tewari, R.K.; Palsaniya, D.R.; Singh, Ramesh; Yadav, R.S.; Venkatesh, A. (Indian Journal of Agroforestry, 2020)
Agroforestry is a proven land use system for vertically enhancing productivity and risk coverage against unstable weather conditions. Inspite of best efforts made in Garhkundar-Dabar watershed in last five years by educating, facilitating and creating water resources which were cited as major bottlenecks inÂ  agroforestry adoption, the pace of adoption remained low. Farmers showed greater inclination towards food crops. Amongst the agroforestry systems demonstrated in the watershed (guava, citrus, Aonla and teak based), guava based agrihorticultural system started fruit production after three years of plantation thereby giving source of additional income. Growth of fruit plants was satisfactory during the study indicating suitability of the systems. Assured availability of water and protection emerged as major determinants of agroforestry land use. Similarly, increased area under vegetables during summers is proving a big boost for agroforestry adoption.